2016
DOI: 10.1387/ijdb.160113sy
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free Xenopus egg extracts for studying DNA damage response pathways

Abstract: In response to a variety of DNA replication stress or DNA damaging agents, the DNA damage response (DDR) pathways are triggered for cells to coordinate DNA repair, cell cycle checkpoints, apoptosis, and senescence. Cell-free Xenopus egg extracts, derived from the eggs of African clawed frogs (Xenopus laevis), have been widely used for studies concerning DDR pathways. In this review we focus on how different experimental systems have been established using Xenopus egg extracts to investigate the DDR pathways th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 104 publications
(139 reference statements)
0
18
0
Order By: Relevance
“…Sperm chromatin was prepared and utilized according to methods as described previously ( 11 , 24 , 35 , 39 ). The preparation of Xenopus LSS, HSS and NPE were described previously ( 35 , 36 , 39 ). DNA synthesis analysis from the HSS/NPE system was performed as previously described ( 11 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm chromatin was prepared and utilized according to methods as described previously ( 11 , 24 , 35 , 39 ). The preparation of Xenopus LSS, HSS and NPE were described previously ( 35 , 36 , 39 ). DNA synthesis analysis from the HSS/NPE system was performed as previously described ( 11 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a cell-free experimental system from eggs of the African clawed frog, Xenopus egg extracts have been widely used in studies of chromosome metabolism, and findings from Xenopus system can be validated in mammalian cell lines ( 33–35 ). Three different types of Xenopus egg extracts have been commonly used: low-speed supernatant (LSS), high-speed supernatant (HSS), and nucleoplasmic extracts (NPE) ( 36–38 ). Here, we have developed a plasmid-based SSB structure at a defined location and found that an ATR-dependent but replication-independent DDR pathway is activated by the defined SSB structure in the Xenopus HSS system.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mechanistic studies using Xenopus system have provided critical insights into the molecular details of DNA repair and DDR pathways in response to DNA double-strand breaks (DSBs) and inter-strand crosslinks (ICLs) [1519]. There are several different types of Xenopus egg extracts: low-speed supernatant (LSS), high-speed supernatant (HSS), and nucleoplasmic extracts (NPE) [20,21]. The detailed approaches to prepare these Xenopus egg extracts have been described previously [7,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Xenopus have already had major contributions to cancer research [for a comprehensive overview see (Hardwick and Philpott, )]. First of all, Xenopus research yielded important knowledge on processes deregulated in cancers such as cell cycle regulation, DNA replication and DNA damage responses, which can be very conveniently studied in Xenopus cell‐free oocyte extracts (Cupello et al ., ; Philpott and Yew, ). Next to this, substantial Xenopus research has focused on developmental signaling pathways such as Wnt, Shh (sonic hedgehog), Notch, TGF‐β (transforming growth factor β), and BMP (bone morphogenetic protein) (Cornell and Eisen, ; Fellgett et al ., ; Gradl et al ., ; Grieco and Hlusko, ; Ishizuya‐Oka and Hasebe, ; Montagner et al ., ; Niehrs, ; Sokol, ; Wang and Steinbeisser, ), which are often hijacked by cancer cells to sustain abnormal growth and to promote cancer progression (Aiello and Stanger, ; Bailey et al ., ).…”
Section: Introductionmentioning
confidence: 99%